2014
DOI: 10.1111/resp.12293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of needle gauge on characterization of endobronchial ultrasound‐guided transbronchial needle aspiration (EBUSTBNA) histology samples

Abstract: A12 Thorax 2012;67(Suppl 2):A1-A204 Introduction Cardiopulmonary Exercise testing (CPET) has become an important tool for perioperative assessment as it may identify patients at risk of postoperative cardiopulmonary complications. Older (1) recommended that an Anaerobic Threshold (AT)<11 or >11ml/min/kg can be used to stratify post-operative treatment in colorectal patients (ITU, HDU or ward). The BTS guidelines (2) recommend that a Peak VO2 (PVO2)<15 or >15ml/ min/kg can be used as a risk assessment in thorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 15 publications
1
55
1
Order By: Relevance
“…Contrary to published data on malignancy phenotyping (27), both needle gauges (22G and 21G) achieved high success rates for EGFR mutation testing without significant differences, although the study may have been underpowered to show this, also considering the 98.75% success rate. The only sample insufficient for EGFR mutation analysis was obtained using a 21G needle.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Contrary to published data on malignancy phenotyping (27), both needle gauges (22G and 21G) achieved high success rates for EGFR mutation testing without significant differences, although the study may have been underpowered to show this, also considering the 98.75% success rate. The only sample insufficient for EGFR mutation analysis was obtained using a 21G needle.…”
Section: Discussioncontrasting
confidence: 50%
“…In our institution, the preferred method of analysis of EBUS-TBNA samples is processing using histopathological techniques (27). However, the majority of previous studies have used cell blocks or needle washings for cytopathological analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 EBUS-TBNA has a high sensitivity and negative predictive value for malignancy in the mediastinal lymph nodes, with quoted sensitivities of between 93-97% and negative predictive values of between 89-97% in recent publications. 1,5,6 There is a paucity of published data relating to EBUS-TBNA in thyroid lesions, but one case series of 12 patients demonstrated EBUS-TBNA correctly detected three malignant cases and was correctly negative in the remaining nine benign cases confirmed on follow-up or further biopsy. 7 In euthyroid, asymptomatic patients, regular follow-up is advised given the risk (albeit low) of malignant transformation.…”
Section: Discussionmentioning
confidence: 94%
“…Two previous cases of pulmonary hamartoma diagnosed with EBUS-TBNA have been reported in the literature using a smaller 22G needle where the findings were suggestive [5,6], however this is the first reported case of linear probe EBUS-TBNA using a 19G needle to diagnose a chondroid hamartoma and with greater confidence from the histological findings. Some published studies have already suggested that using a larger gauge needle at EBUS-TBNA can improve diagnostic rates, particularly in benign disease [7]. Otherwise, cases of chondroid hamartoma usually require either more invasive transbronchial biopsy or surgical biopsy.…”
Section: Discussionmentioning
confidence: 99%